Detecting the Nation: Fictions of Detection and the Imperial Venture - Reitz, Caroline (Ohio State University Press.)
In Detecting the Nation, Reitz argues that detective fiction was essential both to public acceptance of the newly organized police force in early Victorian Britain and to acclimating the population to the larger venture of the British Empire. In doing so, Reitz challenges literary-historical assumptions that detective fiction is a minor domestic genre that reinforces a distinction between metropolitan center and imperial periphery. Rather, Reitz argues, nineteenth-century detective fiction helped transform the concept of an island kingdom to that of a sprawling empire; detective fiction placed imperialism at the center of English identity by recasting what had been the suspiciously un-English figure of the turn-of-the-century detective as the very embodiment of both English principles and imperial authority. She supports this claim through reading such masters of the genre as Godwin, Dickens, Collins, and Doyle in relation to narratives of crime and empire such as James Mill's History of British India, narratives about Thuggee, and selected writings of Kipling and Buchan. Detective fiction and writings more specifically related to the imperial project, such as political tracts and adventure stories, were inextricably interrelated during this time.
JSTOR
Keywords: Detective and mystery stories, English -- History and criticism; English fiction -- 19th century -- History and criticism; Imperialism in literature; Colonies in literature; Police in literature; Great Britain -- Colonies -- In literature; Roman anglais -- 19e siècle -- Histoire et critique; Impérialisme dans la littérature.; Colonies dans la littérature.; Police dans la littérature.; Grande-Bretagne -- Colonies -- Dans la littérature.; English; European; Electronic books